A kind of anti-ultraviolet waterproof membrane
By using linear high-density polyethylene particles, low-density polyethylene particles and ethylene-vinyl acetate and other materials, combined with toughening agents and anti-ultraviolet agents, waterproof coils with high tensile strength and ultraviolet resistance are prepared, which solves the problem of aging of existing waterproof coils in harsh environments and significantly improves their weather resistance and service life.
Patent Information
- Application Number
- CN202410799698.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-06-20
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-06-20
AI Technical Summary
Existing waterproof coils are prone to aging in harsh environments such as sun and rain, high temperature or high cold, resulting in insufficient weather resistance and service life, and are unable to effectively protect buildings.
Linear high-density polyethylene particles (HDPE), linear low-density polyethylene particles (LDPE) and ethylene-vinyl acetate (EVA) are used as the main raw materials, combined with polyethylene octene coelastic toughener (POE), carbon black, antioxidant, anti-ultraviolet agent and stabilizer, and a sheet is made by melt extrusion to prepare a waterproof coil with high tensile strength, elongation and ultraviolet resistance.
It improves the tensile strength, elongation and puncture resistance of the waterproof coil, enhances its tolerance to ultraviolet rays, chemical corrosion and temperature changes, extends service life and improves the durability of the building.
Smart Images

Figure BDA0004902994440000061 
Figure BDA0004902994440000071 
Figure BDA0004902994440000072
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of waterproof coiled materials, and in particular to an anti-ultraviolet waterproof coiled material. Background Art
[0002] The transportation and storage environment of waterproof materials during construction and application is relatively poor, and the protective measures after construction are relatively lagging. Waterproof materials will inevitably experience long-term tests such as sun, rain, high temperature or high cold. Anti-ultraviolet performance can make waterproof membranes have a longer service life and resistance to weather aging; improving the anti-ultraviolet ability of waterproof materials can effectively improve the weather resistance and service life of waterproof materials, and increase the protection period of waterproof materials for buildings, making buildings more durable. Therefore, improving the anti-ultraviolet ability of waterproof materials is an important performance indicator of the competitiveness of waterproof materials. Summary of the invention
[0003] In view of this, the purpose of the present invention is to provide an anti-ultraviolet waterproof membrane with good tensile strength, good elongation, strong adaptability to base layer expansion or cracking deformation, resistance to root penetration, resistance to ultraviolet rays, resistance to chemical corrosion, low temperature flexibility and good heat resistance to address the defects of the prior art.
[0004] The technical solution of the present invention is as follows:
[0005] The present application provides an anti-ultraviolet waterproof coiled material. The raw material components of the waterproof coiled material are, by mass: 30-35 parts of linear high-density polyethylene particles (HDPE), 30-35 parts of linear low-density polyethylene particles (LDPE), 25-30 parts of ethylene-vinyl acetate (EVA), 3-5 parts of polyethylene-octene co-elastomer toughening agent (POE), 1.8-2.5 parts of carbon black, 2-3 parts of antioxidant, 2-3 parts of anti-ultraviolet agent, and 0.1-0.3 parts of stabilizer.
[0006] Preferably, the raw material components of the waterproof membrane are, by mass: 32 parts of linear high-density polyethylene particles (HDPE), 32 parts of linear low-density polyethylene particles (LLDPE), 28 parts of ethylene-vinyl acetate (EVA), 4 parts of polyethylene octene co-elastomer toughener (POE), 2 parts of carbon black, 2.5 parts of antioxidant, 2.5 parts of UV inhibitor, and 0.2 parts of stabilizer.
[0007] Preferably, the sheet made of linear high-density polyethylene particles (HDPE) with a grade of TR144, linear low-density polyethylene particles (LLDPE) with a grade of 7042, and ethylene-vinyl acetate (EVA) with a grade of 7350 as main raw materials has excellent tensile strength, elongation at break, and puncture resistance.
[0008] Preferably, polyethylene octene co-elastomer (POE) with a grade of 8150 is used as a toughening agent for the membrane, which can make the waterproof membrane have excellent low-temperature resistance, improve the softness of the waterproof membrane, make the material construction easier, and make the membrane fit better during construction at the node parts without bulging or warping.
[0009] Preferably, the antioxidant includes at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate and tris(2,4-di-tert-butylphenyl) phosphite.
[0010] Preferably, the antioxidant comprises pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylbenzene) phosphite, and the mass ratio of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]:tris(2,4-di-tert-butylbenzene) phosphite is 1:(2-4).
[0011] Preferably, the anti-ultraviolet agent includes at least one of nano zinc oxide, nano magnesium oxide, 4-ethoxycinnamic acid p-tolyl ester, and 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole.
[0012] Preferably, the anti-ultraviolet agent comprises a combination of one of the nano zinc oxide and the nano magnesium oxide and at least one of the 4-ethoxycinnamic acid p-tolyl ester and the 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole.
[0013] Preferably, the anti-ultraviolet agent comprises nano zinc oxide, p-tolyl 4-ethoxycinnamate, and 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole, wherein, by mass ratio, nano zinc oxide: p-tolyl 4-ethoxycinnamate: 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole = 1: (0.2-0.4) (0.9-1.5).
[0014] Preferably, the stabilizer comprises tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite.
[0015] Preferably, the mass ratio of nano zinc oxide to tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite is 1:(0.1-0.3).
[0016] Preferably, by mass ratio, nano zinc oxide: tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite=1:0.2.
[0017] The beneficial effects of the present invention include:
[0018] 1. The prepared waterproof membrane has high tensile strength and strong elongation, which can effectively prevent the natural settlement of the building from damaging the waterproof layer. It has strong anti-puncture ability and can effectively protect the material from being pierced by sharp objects, steel bar heads, and construction waste during the construction process to cause water leakage hazards. The material is soft and the construction is simple.
[0019] Linear high-density polyethylene particles (HDPE), linear low-density polyethylene particles (LLDPE), and ethylene-vinyl acetate (EVA) are used as the main raw materials, supplemented with polyethylene octene co-elastomer toughening agent (POE), antioxidants, and UV inhibitors. After mixing, they are melt-extruded together to form sheets. The sheets have high tensile strength, good elongation, soft material, strong puncture resistance, and excellent resistance to UV radiation and aging.
[0020] Second, using zinc oxide and magnesium oxide as the anti-ultraviolet agent of the waterproof coiled material can keep the tensile performance and puncture resistance of the waterproof coiled material after long-term exposure to ultraviolet rays, thereby improving the service life of the waterproof coiled material. The waterproof coiled material of the present application also provides a new anti-ultraviolet agent formula, which makes the coiled material have excellent weather resistance. The tensile performance and puncture resistance of the waterproof coiled material are not reduced after being stored and constructed in harsh construction sites such as sun and rain, high temperature and severe cold, and strong ultraviolet rays, thereby greatly improving the service life of the waterproof coiled material.
[0021] 3. Using pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] and tris(2,4-di-tert-butylphenyl) phosphite as antioxidants can ensure that the waterproof membrane maintains its tensile properties and puncture resistance after weather aging. DETAILED DESCRIPTION
[0022] The present invention is further described below in conjunction with specific implementation modes.
[0023] Example 1
[0024] An anti-ultraviolet waterproof coiled material, the raw material components of which are, by mass: 32 parts of linear high-density polyethylene particles (HDPE), 32 parts of linear low-density polyethylene particles (LDPE), 28 parts of ethylene-vinyl acetate (EVA), 4 parts of polyethylene octene co-elastomer toughener (POE), 2 parts of carbon black, 2.5 parts of antioxidant, 2.5 parts of anti-ultraviolet agent, and 0.2 parts of stabilizer. The antioxidant includes pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate] and tris(2,4-di-tert-butylbenzene) phosphite, and by mass ratio, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate]:tris(2,4-di-tert-butylbenzene) phosphite=1:3. The anti-ultraviolet agent includes nano zinc oxide, 4-ethoxycinnamic acid p-tolyl ester and 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole, wherein the mass ratio of nano zinc oxide: 4-ethoxycinnamic acid p-tolyl ester: 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole is 1:0.3:1.2. The stabilizer includes tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite, wherein the mass ratio of nano zinc oxide: tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite is 1:0.2.
[0025] According to the above formula, various raw materials are added into a mixer and mixed thoroughly. Then, the mixture is sent into the screw barrel of the extruder by a vacuum suction device. After segmented heating, plasticization, stirring and compression, the mixture is fully plasticized. After reduced pressure filtration, it is extruded into a hot-melt film through a flat die. After calendering and cooling and shaping, the waterproof membrane with a thickness of 1.5mm to 1.8mm is obtained.
[0026] Example 2
[0027] An anti-ultraviolet waterproof coiled material, the raw material components of which are, by mass: 30 parts of linear high-density polyethylene particles (HDPE), 35 parts of linear low-density polyethylene particles (LDPE), 27 parts of ethylene-vinyl acetate (EVA), 5 parts of polyethylene octene co-elastic toughener (POE), 2.2 parts of carbon black, 2.8 parts of antioxidant, 2.5 parts of anti-ultraviolet agent, and 0.18 parts of stabilizer. The antioxidant includes pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butylbenzene) phosphite, and by mass ratio, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate:tris(2,4-di-tert-butylbenzene) phosphite=1:3.5. The anti-ultraviolet agent includes nano zinc oxide, 4-ethoxycinnamic acid p-tolyl ester and 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole, wherein the mass ratio of nano zinc oxide: 4-ethoxycinnamic acid p-tolyl ester: 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole is 1:0.4:1.1. The stabilizer includes tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite, wherein the mass ratio of nano zinc oxide: tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite is 1:0.18.
[0028] The preparation method is the same as Example 1.
[0029] Example 3
[0030] A UV-resistant waterproof coiled material, the raw material components of which are, by weight: 35 parts of linear high-density polyethylene particles (HDPE), 30 parts of linear low-density polyethylene particles (LDPE), 30 parts of ethylene-vinyl acetate (EVA), 3 parts of polyethylene-octene co-elastic toughener (POE), 2.5 parts of carbon black, 3 parts of antioxidant, 2.8 parts of UV-resistant agent, and 0.22 parts of stabilizer. The antioxidant includes pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylbenzene) phosphite, and by weight ratio, pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]:tris(2,4-di-tert-butylbenzene) phosphite=1:4. The anti-ultraviolet agent includes nano zinc oxide, 4-ethoxycinnamic acid p-tolyl ester and 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole, wherein the mass ratio of nano zinc oxide: 4-ethoxycinnamic acid p-tolyl ester: 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole is 1:0.4:1.4. The light stabilizer includes tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite, wherein the mass ratio of nano zinc oxide: tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite is 1:0.22.
[0031] The preparation method is the same as Example 1.
[0032] In order to demonstrate the beneficial effects of the present invention, the following comparative examples are also made:
[0033] Comparative Example 1
[0034] A UV-resistant waterproof coiled material, wherein the raw materials thereof do not contain a polyethylene-octene co-elastomer toughening agent (POE), and the formulas and proportions of other components and the preparation method are the same as those in Example 1.
[0035] Comparative Example 2
[0036] An anti-ultraviolet waterproof coiled material, the raw materials of which do not contain nano zinc oxide, and the formulas and proportions of other components and the preparation method are the same as those in Example 1.
[0037] Comparative Example 3
[0038] An anti-ultraviolet waterproof coiled material, wherein the raw materials thereof do not contain 4-ethoxycinnamic acid p-tolyl ester, and the formula and proportion of other components and the preparation method are the same as those in Example 1.
[0039] Comparative Example 4
[0040] An anti-ultraviolet waterproof coiled material, wherein the raw materials thereof do not contain 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole, and the formula and proportion of other components and the preparation method are the same as those in Example 1.
[0041] Comparative Example 5
[0042] An anti-ultraviolet waterproof coiled material, wherein the raw materials thereof do not contain tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite, and the formula and proportion of other components and the preparation method are the same as those in Example 1.
[0043] Comparative Example 6
[0044] An anti-ultraviolet waterproof coiled material, wherein the anti-ultraviolet agent in the raw materials includes nano zinc oxide, p-tolyl 4-ethoxycinnamate and 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole, wherein the mass ratio of nano zinc oxide: p-tolyl 4-ethoxycinnamate: 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole is 1:1:0.5. The formula and proportion of other components and the preparation method are the same as those in Example 1.
[0045] Comparative Example 7
[0046] An anti-ultraviolet waterproof coiled material, wherein the anti-ultraviolet agent in the raw materials includes nano zinc oxide, p-tolyl 4-ethoxycinnamate and 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole, wherein the mass ratio of nano zinc oxide: p-tolyl 4-ethoxycinnamate: 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole is 1:0.1:2. The formula and proportion of other components and the preparation method are the same as those in Example 1.
[0047] Comparative Example 8
[0048] An anti-ultraviolet waterproof coiled material, calculated by mass ratio, nano zinc oxide: tris (1,2,2,6,6-pentamethylpiperidinyl) phosphite = 1:0.05, the formula and proportion of other components and the preparation method are the same as those in Example 1.
[0049] According to the requirements of relevant national standards for products, various performance indicators of Examples 1-3 and Comparative Example 1 and the anti-ultraviolet performance of Example 1 and Comparative Examples 2-8 were tested. The relevant data are shown in Tables 1 and 2.
[0050] Table 1 Test results of products prepared in Example 1 and Comparative Example 1
[0051]
[0052]
[0053] Table 2 Anti-ultraviolet performance of products
[0054]
[0055] It can be seen from the test data in Table 1 that the anti-ultraviolet waterproofing membranes prepared in Examples 1 to 3 of the present invention have excellent mechanical properties and anti-aging properties, and can meet the construction indicators. At the same time, it can be seen from the test data in Table 2 that the anti-ultraviolet agent formula disclosed in the present invention enables the prepared waterproofing membrane to have excellent anti-ultraviolet properties.
[0056] Regarding Comparative Example 1, since its raw materials do not contain polyethylene octene co-elastomer toughening agent (POE), Comparative Example 1 is inferior to Example 1 in tensile properties, low-temperature flexural properties, thermal aging, and alkali resistance.
[0057] Regarding Comparative Example 2, the anti-ultraviolet agent in its raw materials does not contain nano zinc oxide, and the tensile retention rate and elongation retention rate after ultraviolet aging are both reduced.
[0058] Regarding Comparative Example 3, in which the raw materials do not contain p-tolyl 4-ethoxycinnamate, both the tensile retention and the elongation retention after ultraviolet aging decrease.
[0059] Regarding Comparative Example 4, the raw materials thereof do not contain 2-(2'-hydroxy-3',5'-di-tert-phenyl)-5-chlorobenzotriazole, and both the tensile retention rate and the elongation retention rate after ultraviolet aging decrease.
[0060] Regarding Comparative Example 5, in which the raw materials do not contain tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite, both the tensile retention and the elongation retention after ultraviolet aging decrease.
[0061] Regarding Comparative Examples 6, 7 and 8, the ratio of the anti-ultraviolet agent is not within the scope of the present application, so that the tensile retention rate and the elongation retention rate after ultraviolet aging are reduced. From Comparative Examples 6 to 8, it can be seen that the anti-ultraviolet performance of Example 1 is better through the synergistic combination of the anti-ultraviolet agent and the stabilizer within the ratio range of the present application.
[0062] The above-mentioned embodiments only express several implementation methods of the present invention, and the description thereof is relatively specific and detailed, but it cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that, for ordinary technicians in this field, several variations and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention. Therefore, the protection scope of the patent of the present invention shall be subject to the attached claims.
Claims
1. An anti-ultraviolet waterproof coiled material, characterized in that: The raw material components of the waterproof coiled material are, by mass: 30-35 parts of linear high-density polyethylene particles, 30-35 parts of linear low-density polyethylene particles, 25-30 parts of EVA, 3-5 parts of polyethylene octene co-elastomer toughening agent, 1.8-2.5 parts of carbon black, 2-3 parts of antioxidant, 2-3 parts of anti-ultraviolet agent, and 0.1-0.3 parts of stabilizer; The anti-ultraviolet agent comprises nano zinc oxide, 4-ethoxycinnamic acid p-tolyl ester, and 2-(2'-hydroxy-3', 5'-di-tert-butylphenyl)-5-chlorobenzotriazole, wherein, by mass ratio, nano zinc oxide: 4-ethoxycinnamic acid p-tolyl ester: 2-(2'-hydroxy-3', 5'-di-tert-butylphenyl)-5-chlorobenzotriazole=1: (0.2-0.4) (0.9-1.5).
2. The anti-ultraviolet waterproof coiled material according to claim 1, characterized in that: The raw material components of the waterproof membrane are, by mass: 32 parts of linear high-density polyethylene particles, 32 parts of linear low-density polyethylene particles, 28 parts of EVA, 4 parts of polyethylene-octene co-elastomer toughening agent, 2 parts of carbon black, 2.5 parts of antioxidant, 2.5 parts of anti-ultraviolet agent, and 0.2 parts of stabilizer.
3. The anti-ultraviolet waterproof coiled material according to claim 1, characterized in that: The antioxidant includes at least one of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate and tris(2,4-di-tert-butylphenyl) phosphite.
4. The anti-ultraviolet waterproof coiled material according to claim 3, characterized in that: The antioxidant comprises pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate] and tris(2,4-di-tert-butylbenzene) phosphite, wherein the mass ratio of pentaerythritol tetrakis[β-(3,5-di-tert-butyl-4-hydroxyphenyl)propionate]:tris(2,4-di-tert-butylbenzene) phosphite is 1:(2-4).
5. The anti-ultraviolet waterproof membrane according to claim 1, characterized in that: The stabilizer includes tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite.
6. The anti-ultraviolet waterproof coiled material according to claim 5, characterized in that: Calculated by mass ratio, nano zinc oxide: tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite = 1: (0.1-0.3).
7. The anti-ultraviolet waterproof coiled material according to claim 6, characterized in that: Calculated by mass ratio, nano zinc oxide: tris(1,2,2,6,6-pentamethylpiperidinyl)phosphite=1:0.2.
Citation Information
Patent Citations
Ultraviolet-resistant high and low temperature-resistant composition, waterproof coiled material as well as preparation method and application of waterproof coiled material
CN117801411A